2017
DOI: 10.1007/s12602-017-9345-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrophobic Amino Acid Substitutions on Antimicrobial Peptide Behavior

Abstract: Antimicrobial peptides (AMPs) are naturally occurring components of the immune system that act against bacteria in a variety of organisms throughout the evolutionary hierarchy. There have been many studies focused on the activity of AMPs using biophysical and microbiological techniques; however, a clear and predictive mechanism toward determining if a peptide will exhibit antimicrobial activity is still elusive, in addition to the fact that the mechanism of action of AMPs has been shown to vary between peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 66 publications
7
68
1
Order By: Relevance
“…Numerous studies on AMPs and peptidomimetic polymers have shown that this balance plays a key role in antimicrobial activity, cytotoxicity, and interactions with lipid bilayers. [ 41,43,49,62 ] In the peptides presented here, the overall hydrophobic balance is not significantly impacted as E➔Q➔K changes at position 4 are all polar. Notably, Gln is an uncharged polar residue which is naturally less polar than Lys, but does not result in major differences in lipid bilayer binding or antimicrobial activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies on AMPs and peptidomimetic polymers have shown that this balance plays a key role in antimicrobial activity, cytotoxicity, and interactions with lipid bilayers. [ 41,43,49,62 ] In the peptides presented here, the overall hydrophobic balance is not significantly impacted as E➔Q➔K changes at position 4 are all polar. Notably, Gln is an uncharged polar residue which is naturally less polar than Lys, but does not result in major differences in lipid bilayer binding or antimicrobial activity.…”
Section: Discussionmentioning
confidence: 97%
“…Using a series of well‐characterized biophysical/spectroscopic measurements as well as microbiological and cellular assays, the activity of these L1 sequences was investigated. [ 14,17,38‐44 ] Due to the inherent environmental sensitivity of Trp fluorescence emission, the native Trp in the L1 sequence (W6) was exploited as a spectroscopic probe for the oligomerization in solution, bilayer binding, and bilayer orientation of peptides. Antibacterial, bacterial membrane permeabilization, and hemolysis assays were also conducted to evaluate the activity of these sequences against natural biological membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, helical wheel projections of melimine and Mel4 show that the hydrophobic amino acids in melimine segregate to one side of the molecule, whereas as there are no hydrophobic amino acids in Mel4 that can segregate (Figure 7). The lack of the non-polar amino acids Ile and Leu which can encourage peptide binding and disruption of cell membranes (33) may also affect the initial mode of action of Mel4. A recent study (53) has demonstrated that Mel4 does not interact with lipid spheroids composed of 1-oleoyl-2-hydroxy-sn-glycero-3-phosphocholine (PC 18:1) or tethered lipid bilayers composed of 70% zwitterionic C20 diphytanyl-glycero-phosphatidylcholine lipid and 30% C20 diphytanyl-diglyceride ether whilst melimine can interact with these lipid layers.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan is known to be a highly lipophilic amino acid (29), and many cationic peptides contain tryptophan as an important part of their mode of action (30-32). Similarly, other non-polar amino acids such as Leu and Ile can encourage peptide binding and disruption of cell membranes (33). Given that both the peptides have been extensively investigated with human clinical trials, their bactericidal mechanism is relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, less hydrophobic monomers were used allowing block structures to maintain antimicrobial efficacy. This suggests that the type of hydrophobic monomers is an important consideration for antimicrobial polymers with clustered/block formations, especially with highly hydrophobic functional groups such as phenylethyl …”
Section: Figurementioning
confidence: 99%